KEDAI KOPI DAN KOMUNITAS SENI SEBAGAI WUJUD RUANG PUBLIK MODERN - Eka Perwitasari Fauzi (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2019)
This paper is based on research on coffee shops as a modern public space in the information age. This study tries to examine the existence of modern public space in the form of social communities along with more coffee shop emerges as new business trends in Jakarta. One of many coffee shop business is Kedai Suguh Kopi in the West Jakarta Region. In contrast to the concept of a cafe, or a coffee shop which mostly serves only coffee and stunning interior design that might lurks customer for their so-called “instagramable”, one interesting thing about this shop is that coffee is not served to release the sleepy feeling but it witness and become a reason of the birth of an art community that contains freedom of expression without pressure.